2017
DOI: 10.1002/mp.12620
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric consequences of gold nanoparticle clustering during photon irradiation

Abstract: The findings provide grounds for reconciling the observations of cell survival with Monte Carlo predictions of GNP dose enhancement. This work is significant because it demonstrates that GNP clustering needs to be understood and accounted to optimize local dose enhancement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…Similarly, a previous study 20 also found that when a cluster (with separation distance, SD 1 nm) of gold nanoparticles (GNPs, with r = 50 nm) randomly distributed in a water phantom is irradiated with a keV external photon beam, the secondary electrons produced from neighboring GNPs contribute to local dose in the periphery of a GNP and thus enhance dose. On the other hand, another study 38 found that for closely packed GNPs (with r = 25 nm) in a three-dimensional hexagonal arrangement, the clustering mitigates dose enhancement due to the self- absorption by the GNPs for both keV and MeV external photon beam irradiation. These results suggest in both RNT and external beam radiotherapy, the clustering effect on dose enhancement depends on the size and density of the nanoparticles as well as the cluster geometry.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, a previous study 20 also found that when a cluster (with separation distance, SD 1 nm) of gold nanoparticles (GNPs, with r = 50 nm) randomly distributed in a water phantom is irradiated with a keV external photon beam, the secondary electrons produced from neighboring GNPs contribute to local dose in the periphery of a GNP and thus enhance dose. On the other hand, another study 38 found that for closely packed GNPs (with r = 25 nm) in a three-dimensional hexagonal arrangement, the clustering mitigates dose enhancement due to the self- absorption by the GNPs for both keV and MeV external photon beam irradiation. These results suggest in both RNT and external beam radiotherapy, the clustering effect on dose enhancement depends on the size and density of the nanoparticles as well as the cluster geometry.…”
Section: Resultsmentioning
confidence: 99%
“…We carried out both macroscopic and microscopic Monte Carlo simulations to reveal how GNP cluster formation affects the energy deposition to the GNPs and surrounding medium. Several groups previously investigated the effect on dose enhancement of clustered GNPs to the water medium, using models in which GNPs are densely packed and in direct contact with each other [28,29]. Our study modeled GNP clusters by using the parameters given by Peckys and De Jonge (who suggested that GNPs are packed inside vesicles) [24].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Zygmanski et al simulated the dose enhancement in simple planar array and slab cluster models and showed saturation of dose enhancement as the number of GNPs in the cluster increased [27]. Planar or hexagonally packed GNP clusters were previously investigated by other groups [28,29]. On the other hand, quantitative image analysis suggested that GNPs in clusters can actually become trapped inside vesicles [24].…”
mentioning
confidence: 99%
“…22 On the other hand, when the NPs aggregate, the secondary electrons from the inner NP are more likely to be reabsorbed, rendering the outermost NPs to contribute to the dose enhancement. 23 In the Fig. 7, one can notice that the enhancement is localized at the very close vicinity of the discs, with a dose enhancement of approximately 5-fold observed within 0.5 mm around the microdisc, when the microdisc is perpendicular to the beam direction.…”
Section: Simulationsmentioning
confidence: 87%